Kegentingan yang Memaksa dalam Pembentukan Peraturan Pemerintah Pengganti Undang-Undang (Perppu) Nomor 1 Tahun 2022 : Studi Mengenai Pemilihan Umum di Papua - Patty, Johny Harry Isabela (Universitas Proklamasi 45, 2023)
The primary purpose of this research is to examine and find out the causes of the concept of urgency compelling in the formation of Peraturan Pemerintah Pengganti Undang-Undang (Perppu) Number 1 of 2022 to replace Law Number 7 of 2017 concerning general elections in Papua. The approach method used is normative juridical. This approach is intended to be a type of descriptive research concerning laws. Furthermore, the specification of this research is descriptive-analytical. Methods of data collection using library research that tests the document materials and library materials used in this study. The data were analyzed qualitatively normative, namely conducting research by interpreting and constructing statements contained in statutory regulations.This research discusses the formation of government regulation in lieu of law for changes to law Number 7 of 2017 concerning general elections in Papua, considering that extraordinary policies and steps are needed to anticipate the impact of the formation of four new provinces namely South Papua, Central Papua, Papua Mountains, and Southwest Papua. It is intended that the 2024 Election will continue according to schedule and stages so as to create domestic political stability.